EFFORT OF LOCAL TOURISM DEVELOPMENT: COMMUNITY PARTICIPATION IN PATAAN TEMPLE'S DEVELOPMENT, LAMONGAN REGENCY - Eni Febrianti; Asep Sumaryana; Heru Nurasa (Natapraja, 2026)
This study aim to analyse the participation of the Pataan Village community in developing local heritage tourism at Pataan Temple by examining the strength of the network. The analytical framework of this study draws on Tosun's theory of community participation. This study employs a qualitative research method, collecting data through observation, interviews, and documentation. The analysis in this study uses an interactive model and is supported by network analysis in MAXQDA and Gephi. The findings of the study show that the awareness possessed by the community is very high in participating in helping programs provided by the government, and strong tolerance, even though coexistence with differences of trust is one of the strengths in implementing tourism development policies and programs. The village selametan tradition support community to remain compact and harmonious and used as an annual village tradition that continues to be held, a tradition that is believed not only as a form of gratitude but as a culture to maintain the value of integrity and the sacred value of the culture of the people of Pataan Village. And supported by the natural potential around the temple, which can be developed into a tourist attraction, namely Bukit Godanan and a large spring source for the local mineral water product of the village. However, in reality, awareness in conveying ideas, and even decision-making is still very minimal. Most forms of community participation are still implemented, not as planners, formulators and managers of both policies and programs.